Description of the Knowledge Level of Students of SMPN 1 Batang Kapas About Adolescent Reproductive Health - Refa Rahmaddiansyah; Sukarsi Rusti; Fettriwanti Fettriwanti (Lembaga Pengembangan Kinerja Dosen, 2023)
Reproductive health is one of the national and global development targets based on the 2030 sustainable development goals. The prominent problems among adolescents are grouped into three risks or the KRR Triad. Correct knowledge and good understanding of reproductive health can direct a teenager towards responsible sexual behavior. The purpose of this study was to describe the level of knowledge about adolescent reproductive health among students at SMPN 1 Batang Kapas. The research design uses a purely descriptive study using a quantitative approach. The sample in this study were 26 students of SMPN 1 Batang Kapas who fit the inclusion and exclusion criteria. Questionnaires are used as research data collection tools. The data were then analyzed univariately using the SPSS application. The average age of the respondents was 13.23 years with the youngest being 12 years and the oldest being 15 years. Respondents consisted of 8 men (30.76%) and 18 women (69.24%). The level of knowledge about reproductive health is good at 73.08% or 19 people. While the remaining 7 people (26.92%), have a sufficient level of knowledge. The majority of respondents have a good level of knowledge about adolescent reproductive health. This is because respondents have received information about reproductive health before. Provision of information sources is significantly related to adolescent knowledge regarding fertility, sexual intercourse, marriage plans, and the lowest safe age for childbirth so that it will encourage the formation of positive sexual behavior. The level of knowledge about reproductive health in this study is in the good category. It is hoped that this level of knowledge can lead to good reproductive behavior and function.